A generalized overview of antibiotic resistance on the context of South Asian countries - Rahman, Ahsab; Rafey, Fatima Fidatur (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2022.